Legal Certainty of Electronic Certificates as Evidence of Land Ownership in Indonesian Agrarian Law - Hutomo, Putra; Yuhelson, Yuhelson; Achmad Darodjat, Tubagus (International Journal of Social Science, Education, Communication and Economics, 2024)
The position of electronic certificates in agrarian law in Indonesia is a means of proof of ownership of land rights, ownership rights to apartment units, management rights, and mortgage rights, The Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 5 of 2017 concerning Electronic Land Information Services (hereinafter referred to as Ministerial regulations ATR/Head of BPN 5/2017) which was later replaced by Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 19 of 2020 concerning Electronic Land Information Services (hereinafter referred to as Ministerial regulations ATR/Head of BPN 19/2020). Ministerial regulations ATR / Head of BPN 5/2017 is the forerunner or embryo of the start of electronic land law politics in Indonesia. For this reason, in order to further realise the certificate, the Indonesian Government should regulate the position of electronic certificates in law and need to support changes in the registration system in Indonesia to a positive system with the issuance of electronic certificates, in addition to conducting comprehensive socialisation to the Indonesian people who think that they do not hold physical evidence of certificates with the assumption that everything is electronically based.